MULTICULTURAL EDUCATION AS A PROACTIVE STRATEGY TO ADDRESS THE ISSUE OF NATIONAL DISINTEGRATION - Fitri Nanda Shafira Fitri; Arda Ami Guspina; Fany Primandari; Rafly Izza Pramudia (Journal of Pedagogical Content Knowledge, 2026)
Indonesia, as a country with a diversity of ethnic groups, religions, races, cultures, and languages, faces challenges in maintaining national unity amid the potential for national disintegration. One approach that can be applied to strengthen social integration is through multicultural education. This study aims to analyze the role of multicultural education as a proactive strategy in preventing national disintegration. The study employs a qualitative approach using a literature review method, involving the collection and analysis of various relevant scholarly sources, including journal articles, books, and other academic documents. Data analysis was conducted using a descriptive-analytical approach by identifying concepts, findings, and practices of multicultural education that support the strengthening of unity. The results of the study indicate that multicultural education contributes to instilling values of tolerance, mutual respect, inclusivity, justice, and respect for diversity, thereby shaping students’ character to foster national consciousness and a commitment to unity. Nevertheless, its implementation still faces various challenges, including limited teacher competencies, suboptimal integration of multicultural values into the curriculum, and the influence of social polarization in the digital age. Therefore, the strengthening of multicultural education must be carried out continuously through synergy among schools, families, communities, and the government as a preventive measure to maintain the integrity of the Unitary State of the Republic of Indonesia.